The seroprevalence of cystic hydatidosis in Oman - Idris, Mohamed; Ruppel, Andreas; Gehrig-Feistel, Hannelore; Alansari, A. S.; al-Rejaibi, A. K.; Tageldin, M. H.; el-Sinary, K. (Annals of tropical medicine and parasitology, 1999)
The presence of antibodies against Echinococcus granulosus in sera from 306 humans and 390 camels in Oman was investigated by indirect haemagglutination assays. Only one of the human and five of the camel sera gave positive reactions. The reactivities of the human sera were confirmed by ELISA. These results, together with isolated reports of hydatid cysts, indicate that E. granulosus is endemic in Oman, although with a low prevalence.
Gesehen am 14.04.2021